Surveillance for leptospirosis in the Americas, 1996-2005: a review of data from ministries of health - Federico Costa; Martha Sílvia Martinez-Silveira; José E. Hagan; Rudy A. Hartskeerl; Mitermayer Galvão dos Reis; Albert I. Ko (2012)
OBJECTIVE: To characterize current leptospirosis reporting practices in the Americas. METHODS: Information was collected from the official websites of national ministries of health from the Americas region and two international organizations; personal communications; and three international morbidity databases. For all sources other than the morbidity databases, the review was limited to official reports citing clinically suspected and laboratory confirmed leptospirosis cases or deaths during the period 1996-2005. RESULTS: A total of 73 out of 1 644 reports met the selection criteria and were included in the analysis. Published leptospirosis data were available from half of the countries/sovereign territories (24 out of 48), and 18 of them had mandatory notification policies for leptospirosis. The sum of the median number of leptospirosis cases notified annually by the 24 countries/territories was 4 713.5, but just three countries (Brazil, Costa Rica, and Cuba) accounted for 83.1% (3 9cas20 es) of the notifications. Eight (16.7%) countries reported deaths due to leptospirosis. The sum of the median number of deaths reported annually for the eight countries was 380, but 349 (91.8%) were reported by Brazil. CONCLUSIONS: Notification practices in the Americas for leptospirosis are limited. Therefore, the numbers of cases and deaths reported are not representative for the region. The lack of leptospirosis data for many countries/territories may reflect weaknesses in certain aspects of national surveillance systems, including mandatory reporting policies, clinical laboratory infrastructure for performing case confirmation, and capacity to collect reported cases. Improved surveillance of leptospirosis cases and deaths in the Americas is needed to allow monitoring of regional epidemiological patterns and to estimate the burden of this important disease.